Bilateral failure of adduction following orbital decompression. Issue 4 (April 1990) - Kinsella, F; Kyle, P; Stansfield, A
Abstract : We report a case of bilateral complete failure of adduction following bilateral translid antralethmoidal orbital decompression. We believe the probable mechanism is neuropraxia (temporary dysfunction) of the third cranial nerves' supply to the medial recti, owing to these nerves' occupying an anatomically abnormal position. Partial recovery of adduction occurred over the ensuing six months.